Hollywood Diplomacy : Film Regulation, Foreign Relations, and East Asian Representations - Chung, Hye Seung, 1971- (Book collections on Project MUSE., 2020)
"Hollywood Diplomacy makes the case that, rather than simply reflect the West's cultural fantasies of an imagined 'Orient, ' images of East Asian ethnicities (Chinese, Japanese, and Korean) have long been contested ideological sites where the commercial interests of Hollywood studios and the political mandates of U.S. foreign policy collide, compete against one another, and often become compromised in the process. Hye Seung Chung highlights the mediating capacity of film regulation, presenting it not as an obstacle to artists' freedom of expression, but rather as an enforcer of institutional protection, a facilitator of international relations, and a contributor to 'political correctness' regarding images of racial minorities and foreign nationals. Drawing on archival evidence and film content analysis, Hollywood Diplomacy redefines external censorship or advisory entities (by the Chinese government, the World War II propaganda agency OWI, and the DoD) as productive contributors pushing for increased cultural authenticity and/or more egalitarian racial/ethnic/national images in Hollywood's Orientalist productions. The book is divided into two parts: the first is 'Diplomatic Representations in Classical Hollywood, ' which examines films such as Shanghai Express, The Purple Heart, and Bamboo Prison, and the second is 'The War on Terror, Contemporary Hollywood, and Its Global Discontent, ' which examines films such as Die Another Day and The Interview"--